STRATEGIC MARKETING IN TEACHER EDUCATION: INFLUENCING ADMISSIONS IN INDONESIA'S MADRASAH IBTIDAIYAH PROGRAMS - Devi Fatwanti; Safuroh; Muhammad Saleh; Ilzamudin; Ahmad Qurtubi; Agus Gunawan (Karimiyah: Journal of Islamic Literature and Muslim Society, 2026)
Student program selection has become a strategic concern for higher education institutions, yet empirical evidence on how marketing mix factors influence enrolment decisions in Islamic teacher education remains limited. This study investigates the determinants of prospective students’ admission decisions in Madrasah Ibtidaiyah Teacher Education programs at State Islamic Religious Higher Education Institutions (PTKIN) in Indonesia. Using a quantitative survey of 547 students from three PTKINs, data were collected through a structured Likert-scale questionnaire and analysed using Confirmatory Factor Analysis and regression techniques. The findings identify five key determinants of admission decisions: Influence of Surroundings, Consideration of University, Perceived Usefulness, Social Consideration, and Vocational Aspects. Among these, the Influence of Surroundings emerged as the most dominant factor, indicating the central role of family, peers, and community networks in shaping students’ program choices. Institutional reputation and perceived career prospects also significantly influenced decision-making. This study extends the higher education marketing literature by providing an empirically grounded model of student choice within the marketing mix framework in the context of Islamic higher education.